2001
DOI: 10.1080/00224540109600550
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sex, Gender, Self-Discrepancies, and Self-Awareness on Anger and Verbal Aggressiveness Among U.S. College Students

Abstract: Among a sample of 445 U.S. college students, the authors examined the extent to which individual differences (e.g., sex, gender, self-discrepancies, self-awareness) explained anger tendencies and verbal aggressiveness. Regression analyses showed that (a) the tendency to repress anger (anger-in) was explained by masculinity, desire to be masculine, and public self-awareness, R2 = .19, F(11, 433) = 8.44, p < .001; (b) the tendency to express anger (anger-out) was explained by sex, masculinity, and public self-aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 63 publications
4
27
0
1
Order By: Relevance
“…Anger was low among those females with a higher adherence to feminine traits. This finding may relate to previous findings that explain how anger management is characteristic of feminine traits like emotionality, delicacy or affection (Kinney et al 2001).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Anger was low among those females with a higher adherence to feminine traits. This finding may relate to previous findings that explain how anger management is characteristic of feminine traits like emotionality, delicacy or affection (Kinney et al 2001).…”
Section: Discussionsupporting
confidence: 54%
“…This finding is consistent with previous research and with the idea that people with aggressive tendencies experience anger and hostility. From this viewpoint, it seems logical that if masculine traits are related to proneness to aggression, then these traits also relate with anger and hostility (Kinney et al 2001;Kogut et al 1992).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This point of view was confirmed by many studies, that have revealed differences between men and women about their representation of aggression (Andreu et al, 2002;Archer & Haigh, 1999;Hines & Saudino, 2003;Ramirez, Andreu, & Fujihara, 2001), its justification or acceptability (Archer & McDaniel, 1995;Astin, Redston, & Campbell, 2003;Stewart-Williams, 2002), and its occurrence (Connor, Steingard, Anderson, & Melloni, 2003;Graham & Wells, 2001;Kinney, Smith, & Donzella, 2001;Knight, Guthrie, Page, & Fabes, 2002;Zeichner, Parrott, & Frey, 2003). However, our results limited to attitude toward aggressiveness, did not show such sexual differences; thus, they rather confirmed other studies in which differences between men and women were also absent or minute (Ramirez, Fujihara, & van Goozen, 2001).…”
Section: Discussionsupporting
confidence: 48%
“…Self-awareness generally decreases physical and verbal aggression [Kinney et al, 2001;Prentice-Dunn and Rogers, 1982;Scheier et al, 1974]. These studies typically induced self-awareness by having participants look at themselves in the mirror, take a self-esteem measure, or focus primarily on themselves rather than others.…”
Section: Distinguishing Between Mindfulness Rumination and Related mentioning
confidence: 98%